Service Level Management of Information Technology and System in ITB STIKOM Bali - Nyoman Ayu Nila Dewi; A. A. Ngurah Bima Prasatria (Bina Nusantara University, 2021)
ITB STIKOM Bali is a technology-based university so that all business processes, especially related to academics, student affairs, and finance, utilize information technology. Management of the information system and technology is carried out by the Computer and Network Center unit (Pusat Komputer dan Jaringan - PUSKOMJAR). In the management of Information Technology (IT) services, an agreement is needed in the form of Service Level Management (SLM) which contains the level of service, quality of service, and complaints handling, so users’ needs are aligned with the system developer. Meanwhile, in managing the internal system of ITB STIKOM Bali, the agreement between PUSKOMJAR and related units is only in the form of submitting a form for making or changing the system. Therefore, it raises a problem if there is a mismatch in the manufacture or development of the system because there is no contract document that regulates in detail about the system. Hence, designing an SLM of IT and system services at ITB STIKOM Bali to overcome these problems is necessary. The research presents a case study by analyzing and designing the SLM of service system and IT in ITB STIKOM Bali. The applied research method is literature study and observation, analysis of existing SLM, designing new SLM, and conclusions. The result of the research is a document of SLM for internal IT and system services at ITB STIKOM Bali. Based on the analysis and design of SLM, the SLM document can help the PUSKOMJAR in documenting IT service information and making it easier for users to get information related to the provided IT services.